THE ROLE OF NEW METHOD SCHOOLS IN THE EDUCATIONAL SYSTEM OF TURKESTAN AT THE END OF THE 19TH CENTURY (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The situation that arose in the history of the educational system of the Turkestan region at the end of the 19th century and its impact on the cultural processes of the region are examined. The struggle that arose in the educational arena of the region as a result of the activities of various educational innovations, traditional education, new-method schools, and Russian-system schools is analyzed.